IoT-Based Smart Temple Prototype for Remote Lamp and Loudspeaker Control at Pengulon Traditional Village Temple - Kadek Reda Setiawan Suda; Sri Muntiah Andriami; Muhammad Khalil; Kurnia Dwi Artika; Sukma Firdaus; Muhammad Rezki Fitri Putra (TEPIAN, 2026)
Daily temple operations in Balinese Hindu temples often require caretakers to manually activate and deactivate lamps and loudspeakers, especially for routine prayer activities such as Tri Sandya at 06:00, 12:00, and 18:00. This manual process can be inefficient when operators are unavailable and may cause unnecessary electricity consumption when devices remain active longer than needed. This study develops an Internet of Things (IoT)-based Smart Temple prototype for remote lamp and loudspeaker control at Pengulon Traditional Village Temple. The system was designed using an ESP32 microcontroller, a four-channel relay module, and a web-based interface that enables users to control temple devices through an internet connection. The research applied a prototype development model consisting of communication, quick planning, quick design modelling, prototype construction, deployment, and feedback. Functional testing showed that all connected devices could be activated and deactivated successfully through the web interface. The speaker was activated in 1.51 seconds and deactivated in 2.10 seconds, while the three lamp channels showed activation times between 3.61 and 4.40 seconds and deactivation times between 1.30 and 2.50 seconds. These results indicate that the proposed prototype can support more practical, flexible, and efficient temple device management. The contribution of this study lies in adapting low-cost IoT-based relay control to the operational context of a traditional worship facility, where remote accessibility, ritual scheduling needs, and energy-use efficiency are important practical considerations.